تفسير سورة محمد صلى الله عليه وسلم: دراسة مقارنة بين الطبري وابن أبي حاتم الرازي: The Interpretation of Surah Muhammad: A Comparative Study between Al-Tabari and Ibn Abi Hatim Al-Razi - Daud, Shamsiah; Rababa’h, Mohammad Mjalli (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
Since its emergence, the interpretation of the Quran had encountered complex phases throughout the history of Islamic literature. The Quran had been interpreted with various methods and tafsir bi al-ma’thur (traditional exegesis) and tafsir bi al-ra’y (reason-based exegesis) are among the famous approaches in Quranic exegesis. However, there is one method of interpretation referred to as tafsir muqaranah (comparative exegesis) which is a comparative-contrastive exegetical analysis in which the mufassir (exegete) compares and contrasts between verses with verses or verses with hadith or by various opinion or views of exegetes on an exegetical issue symbolized by a given verse. This method or approach is rarely given an exposure despite being a method formulated and utilized by the early exegetes of formative phase such as al-Tabari and Ibn Abi Hatim al-Razi. Therefore, this study aims to discuss the definition of comparative exegesis and depicting the similarities and differences of the interpretation of al-Tabari and Ibn Abi Hatim al-Razi in selected verses from surah Muhammad (peace be upon Him). It also aims to examine how these differences could be interacted and related to each other and to wider context of the arrival at conclusive interpretation. Data for this study was obtained through the literature review methodology as well as an analysis based on inductive and deductive methods. The paper concludes by saying that there are similarities in both methodologies of al-Tabari and Ibn Abi Hatim particularly in interpreting a verse through al-ma’thur technique. Yet the differences among them could be identified by distinct terminological usage of a word in the same verse. While the establishment of tarjih (preponderance) or selecting among differing opinions could be found in conflicting issue of surah Muhammad verses in order to get the best conclusion of the interpretation.